"Indigenous mathematics": Tensions in teachers' intercultural formation - Mariane Dias Araújo; Vanessa Sena Tomaz (Arizona State University, 2020)
This article analyzes tensions that take place when a Brazilian indigenous student develops research on emerging community issues and establishes relations between practices from indigenous tradition and mathematical practices from school, in the context of an intercultural teacher training undergraduate course. The work is situated on the intercultural field, on the decolonial perspective, and on ethnomathematics, created from the late work of Wittgenstein and Michel Foucault's thought. It is a qualitative perspective, composed by multimodal data from a Pataxó student's research, articulating texts, images, audio of the defense session, an interview, and a questionnaire.  The analysis shows that tensions evolve from power relations between the Western mathematics and the other ways to produce mathematics, in this case, using the traditional knowledge of Pataxó body paint.  Such tensions highlight the impossibility of accepting the existence of a universal mathematical language and legitimates Pataxó mathematics, within their schools, with its own epistemologies based on reasons, cosmovision, and spiritualities.